Conception of Uncertainty and Risk in Economy - Gegužis, Artūras (Ekonomika, 2003)
In every step of our life we face with uncertainty and risk. There are two sectors in the society - institutionalised and uninstitutionalised. The purpose of the institutionalised sector that embodies state, government and industry, is to reduce the level of risk and uncertainty, while the purpose of the uninstitutionalised sector that embodies individuals is to balance between awards and losses for taking risk. The understanding of economic risk depends on the ideology that varies from total ignorance of government for individualism and total ignorance of the market forces for holism. For understanding and knowledge of risk we have to turn into economic science, that has evolutionarily identified such risk and uncertainty factors as stable moral standards, time, space (related with globalisation and consolidation), new technologies and expectations. The latter is the main obstacle to reduce uncertainty and measure risk, as it creates the phenomenon of reflectivity - i.e. when our thinking affects actual results and actual results affects thinking. Reflectivity itself causes a higher level of uncertainty and it worsens a measurability of risk. The author proposes an elasticity of expectations as a measure of reflectivity. The measure of elasticity of expectations shows how expectations react to a change in actual result. The closer the measure is to zero, the lower the reflectivity is. If expectations correspond to actual results the economy is in equilibrium. Particularly the phenomenon of reflectivity is applicable to financial markets that are dominated by speculative capital flows. The speculative capital leads to instability in the markets and may be the reason of economic crisis. Thus the perception that the role of government in the market regulation has to be strengthened becomes stronger and stronger in the world. After making a research of matching expectations and actual result, in the industrial output one can state that the Lithuanian industry that represents the real sector is in a dynamic equilibrium after 2000, as actual results quite strongly correlate with expectations. Values of the measure of elasticity of expectations arc mostly close to zero, thus the reflectivity is quite low and risk is measurable as well as future can be forecasted more exactly. Certainly it is only an assumption as the future is unknowable. Financial sector in Lithuania cannot be characterised as very reflective as Lithuanian financial markets related with speculative capital, i.e. shares and derivatives, is very weak. The reduction of risk can be achieved via insurance, avoidance of risky activities and diversification.